Impaired Spontaneous Baroreceptor Reflex Sensitivity in Patients With COPD Compared to Healthy Controls: The Role of Lung Hyperinflation - Mayr, Anna Katharina; Wieser, Victoria; Funk, Georg-Christian; Asadi, Sherwin; Sperk, Irene; Urban, Matthias Helmut; Valipour, Arschang (Frontiers in Medicine, 2022)
Background and Objectives: Patients with chronic obstructive pulmonary disease (COPD) are at increased risk for cardiovascular disease. This study aimed to investigate the relationship between pulmonary hyperinflation and baroreceptor reflex sensitivity (BRS), a surrogate for cardiovascular risk. Methods: 33 patients with COPD, free from clinical cardiovascular disease, and 12 healthy controls were studied. Participants underwent pulmonary function and non-invasive hemodynamic measurements. BRS was evaluated using the sequence method during resting conditions and mental arithmetic stress testing. Results: Patients with COPD had evidence of airflow obstruction [forced expiratory volume in 1 s predicted (FEV1%) 26.5 (23.3–29.1) vs. 91.5 (82.8–100.8); P < 0.001; geometric means (GM) with 95% confidence interval (CI)] and lung hyperinflation [residual volume/total lung capacity (RV/TLC) 67.7 (64.3–71.3) vs. 41.0 (38.8–44.3); P < 0.001; GM with 95% CI] compared to controls. Spontaneous mean BRS (BRSmean) was significantly lower in COPD, both during rest [5.6 (4.2–6.9) vs. 12.0 (9.1–17.6); P = 0.003; GM with 95% CI] and stress testing [4.4 (3.7–5.3) vs. 9.6 (7.7–12.2); P < 0.001; GM with 95% CI]. Stroke volume (SV) was significantly lower in the patient group [−21.0 ml (−29.4 to −12.6); P < 0.001; difference of the means with 95% CI]. RV/TLC was found to be a predictor of BRS and SV (P < 0.05 for both), independent of resting heart rate. Conclusion: We herewith provide evidence of impaired BRS in patients with COPD. Hyperinflation may influence BRS through alteration of mechanosensitive vagal nerve activity.